PENGARUH LEVERAGE DAN UMUR PERUSAHAAN TERHADAP CSRD PADA PERUSAHAAN PERTAMBANGAN DI INDONESIA - Alicia Wido Belinda; Anita Kusuma Dewi; Nurmala Nurmala (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2023)
This study aims to examine whether there is an influence between leverage and company age on the CSRD of mining companies that are registered or listed on the Indonesia Stock Exchange (IDX) in 2018-2020. CSRD is the dependent variable, while the leverage and firm age variables are independent or independent variables. This study collected data through the purposive sampling method. In taking samples through predetermined criteria, 16 samples were obtained as company samples with an observation period from 2018-2020, which means there were 48 samples. The analysis technique uses multiple regression analysis, which is processed using the SPSS V25 application. The results of this study show that leverage has no effect on CSRD, but company age has a positive impact on CSRD. The company age positively affects CSRD and can be considered by the company in making decisions.